Commensal bacteria signal through TLR5 and AhR to improve barrier integrity and prevent allergic responses to food - Andrea M. Kemter; Robert T. Patry; Jack Arnold; Lauren A. Hesser; Evelyn Campbell; Edward Ionescu; Mark Mimee; Shan Wang; Cathryn R. Nagler (Cell Reports, 2023)
Summary: The increasing prevalence of food allergies has been linked to reduced commensal microbial diversity. In this article, we describe two features of allergy-protective Clostridia that contribute to their beneficial effects. Some Clostridial taxa bear flagella (a ligand for TLR5) and produce indole (a ligand for the aryl hydrocarbon receptor [AhR]). Lysates and flagella from a Clostridia consortium induced interleukin-22 (IL-22) secretion from ileal explants. IL-22 production is abrogated in explants from mice in which TLR5 or MyD88 signaling is deficient either globally or conditionally in CD11c+ antigen-presenting cells. AhR signaling in RORγt+ cells is necessary for the induction of IL-22. Mice deficient in AhR in RORγt+ cells exhibit increased intestinal permeability and are more susceptible to an anaphylactic response to food. Our findings implicate TLR5 and AhR signaling in a molecular mechanism by which commensal Clostridia protect against allergic responses to food.